BENTUK, STRATEGI PENGGUNAAN, DAN KESANTUNAN TINDAK TUTUR MENOLAK DALAM INTERAKSI ANTARMAHASISWA PRODI SASTRA PRANCIS FBS UNNES (Lingua, 2010)
The problems that were examined: (1) how the realization of speech act of refuser in French by the researchsubjects are used? (2) what strategies are used by research subjects in refuser to their partners? and (3) howthe politeness levels are used in the Speech Act of refuser by Semester VI Students?Data obtained by â€œfishingâ€ techniques, â€œfishingâ€ the respondents using a questionnaire. The data wereanalyzed using equivalent analytical methods subtypes with a pragmatic â€œtool partners of the respondents" (thelittle brother, their lover, their rector, and their parking worker) and the power of mental sort (referential) ownedby the researcher.The results showed that (1) of the realization of the speech act refuser, the respondents prefered the"declarative" mode to reject the partners than the other modes, both single mode and dual mode, (2) from thepoint of strategy used to "reject" partner respondents, most respondents tended to reject "indirectly" because itallows both participants involved in feel â€œface savingâ€, and (3) of the level politeness in the use of strategies,respondents tend to use the level politeness "very polite" and "polite" to others (lovers, rectors, and parkingworker) and tend to "not polite" to the little brother/sister.Keywords: pragmatic, speech act, realization, strategy, levels of politeness